A stable sensorless control of AC machines - Ker, Jason Wei Xiang (Nanyang Technological University, 2022)
In recent years, sensorless AC machine drives applications have expanded in industrial to household electrical appliances. The advantages of sensorless motor drives include lower cost, increased reliability, reduced hardware complexity, and lesser maintenance requirements. Various control methods are available and classified as Field-Oriented Control (FOC), adaptive reference observer-based, signal injection, and direct motor control.